2022
DOI: 10.1093/plphys/kiac387
|View full text |Cite
|
Sign up to set email alerts
|

The trans-Golgi-localized protein BICAT3 regulates manganese allocation and matrix polysaccharide biosynthesis

Abstract: Manganese (Mn2+) is essential for a diversity of processes, including photosynthetic water splitting and the transfer of glycosyl moieties. Various Golgi-localized glycosyltransferases that mediate cell wall matrix polysaccharide biosynthesis are Mn2+-dependent, but the supply of these enzymes with Mn2+ is not well understood. Here, we show that the BIVALENT CATION TRANSPORTER 3 (BICAT3) localizes specifically to trans-cisternae of the Golgi. In agreement with a role in Mn2+ and Ca2+ homeostasis, BICAT3 rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 107 publications
0
14
0
Order By: Relevance
“…Mutation of Golgi Mn transporters TM9SF4 (a V-type ATPase-associated protein belonging to the Golgi-resident TMN family member) and TMEM165 (Ca/Mn pump, a calcium-permeable channel), which are responsible for transport of Mn or other metals in or out of the Golgi, also cause dysfunctions in cell division and differentiation in mammalian cells that evoke pathogenesis and clinical diseases [ 17 , 30 , 32 , 33 ]. The importance of Golgi Mn homeostasis has also been demonstrated by several non-TM9 family transport proteins, such as AtMTP11 [ 25 ], OsMTP11 [ 34 , 35 , 36 ], PML3 (UPF0016) [ 37 ], BnMTP9 [ 38 ], and BICAT3 (BIVALENT CATION TRANSPORTER 3) [ 39 ], and disruption of these transport proteins can lead to impaired growth and development by blocking vesicle secretory pathways or cell wall polysaccharide biosynthesis under elevated or normal Mn supply conditions. These results strongly suggest that OsTMN11-mediated Mn homeostasis is also necessary to maintain the processing of growth-related proteins in the Golgi.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Golgi Mn transporters TM9SF4 (a V-type ATPase-associated protein belonging to the Golgi-resident TMN family member) and TMEM165 (Ca/Mn pump, a calcium-permeable channel), which are responsible for transport of Mn or other metals in or out of the Golgi, also cause dysfunctions in cell division and differentiation in mammalian cells that evoke pathogenesis and clinical diseases [ 17 , 30 , 32 , 33 ]. The importance of Golgi Mn homeostasis has also been demonstrated by several non-TM9 family transport proteins, such as AtMTP11 [ 25 ], OsMTP11 [ 34 , 35 , 36 ], PML3 (UPF0016) [ 37 ], BnMTP9 [ 38 ], and BICAT3 (BIVALENT CATION TRANSPORTER 3) [ 39 ], and disruption of these transport proteins can lead to impaired growth and development by blocking vesicle secretory pathways or cell wall polysaccharide biosynthesis under elevated or normal Mn supply conditions. These results strongly suggest that OsTMN11-mediated Mn homeostasis is also necessary to maintain the processing of growth-related proteins in the Golgi.…”
Section: Discussionmentioning
confidence: 99%
“…These cell wall defects in bicat3 are likely the result of reduced glycosyltransferase activity in the Golgi and suggest that other Mn 2+ -transport proteins, like ECA3, cannot (fully) replace BICAT3 function. Surprisingly, comparing bicat3 and eca3 plants, He et al 2022 found that photosynthesis was improved in eca3 in their hydroponic experimental set-up, albeit less pronounced than in bicat3 . This contrasts with previous findings using in vitro grown seedlings that show severely reduced chlorophyll content in eca3 ( Mills et al, 2008 ), suggesting decreased photosynthesis.…”
mentioning
confidence: 91%
“… He et al (2022) found that the loss of BICAT3 led to higher Mn 2+ concentration in shoots under Mn deficiency, and photosynthesis was improved in bicat3 . Mn 2+ analysis of isolated chloroplasts revealed higher chloroplast Mn 2+ content, strongly suggesting that this is the reason for the higher overall shoot Mn 2+ concentration.…”
mentioning
confidence: 94%
See 2 more Smart Citations